2017
DOI: 10.3390/met7090382
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Heat-Treatments Effect on High Strength Ductile Cast Iron Welded Joints

Abstract: Nowadays, ultimate tensile strengths above 400 MPa become usual for ductile irons, thus allowing the implementation of new design paradigms. Large concentrations of carbon and other influencing elements can negatively interfere with the welding process of ductile cast irons. Efforts made by researchers have led to the discovery of solutions which enable good enough operational results to consider welding as a viable repairing or joining method. Although these alloys have been available for quite some time, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…A similar effect is produced when performing further welding passes relative to the former ones. In a recent study, authors found that when welding a similar high strength DCI to the one discussed in this work, a pre-heating stage of 300 • C for 2 h along with multi-pass welds promoted the best outcome in terms of mechanical properties [24]. Buttering was used successfully in the preparation of the SMAW process, conferring a higher ductility to the weldment [19].…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…A similar effect is produced when performing further welding passes relative to the former ones. In a recent study, authors found that when welding a similar high strength DCI to the one discussed in this work, a pre-heating stage of 300 • C for 2 h along with multi-pass welds promoted the best outcome in terms of mechanical properties [24]. Buttering was used successfully in the preparation of the SMAW process, conferring a higher ductility to the weldment [19].…”
mentioning
confidence: 56%
“…The temperatures profiles were chosen based on the work developed in [20,24], consisting of either 300 • C or 700 • C heat cycles for pre-heating treatments and either 700 • C or 800 • C for PWHT. A map of the sequence/parameters used for each group of samples can be seen in Table 2.…”
Section: Heating Cycle Parametersmentioning
confidence: 99%
See 3 more Smart Citations